In-Class versus Out-of-Class Flipped Classroom Models in English as a Foreign Language Writing - SENGUL, Fatma (2021)
A flipped classroom model is an indispensable part of the English as a foreign language (EFL) writing courses as it helps the instructor to advance the learners’ writing proficiency levels (Pavanelli, 2018). However, EFL students’ attitudes toward the in-class and out-of-class writing models in a flipped classroom process are unknown. Understanding these issues have a vital importance as these will help educators arrange their writing classes based on the flipped classroom models in order to have an effective writing course in line with EFL students’ needs (Abaeian & Samadi, 2016). Therefore, this study purposed to investigate the EFL students’ attitudes toward in-class and out-of-class writing models in a flipped classroom. A quantitative research design was employed through the use of a questionnaire which was employed to 30 EFL students studying at a private university’s English language teaching department. As the findings showed, although the EFL students had positive attitudes towards both flipped classroom models for writing, they preferred the out-of-class model and the majority of them stated that they prefer to produce their written work out-of-class settings. As a consequence of these, EFL educators should use an out-of-class  flipped classroom model for writing, if they give priority to their EFL students’ attitudes towards the writing models on account of having an effective writing course.